Analisis Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Dengan Disiplin Kerja Sebagai Variabel Intervening - Rendi Saputra; Suwarto; Dharmawan (Universitas Muhammadiyah Metro, 2026)
Research aims to analyze the effect of compensation and motivation on employee performance with work discipline as an intervening variable. This research uses a quantitative approach with survey methods. Data was collected through questionnaires distributed to 31 employees at Multimart Batang Hari, East Lampung. Data analysis was carried out using path analysis to test the relationship between research variables. The research results show that compensation has a positive influence on employee performance. Motivation was also found to have a positive influence on employee performance. In addition, work discipline has been proven to act as an intervening variable that strengthens the relationship between compensation and motivation and employee performance. In other words, high work discipline increases the positive effects of compensation and motivation on employee performance.